Chapter 7 Estimating chemical and microstructural heterogeneity by correlating relaxation and diffusion - Tax, Chantal M.W (Royal Society of Chemistry, 2020)
Whereas diffusion NMR can probe the structural configurations configurations of microscopic environments in biological tissue, relaxation can provide complementary information on their chemical composition. This chapter considers experiments in which diffusion diffusion and relaxation properties are sampled simultaneously by varying multiple acquisition parameters. As such, correlations between the diffusion and relaxation can be established, providing an altogether more complete picture of heterogeneous tissue.